ANALISIS PENGARUH CUSTOMER ONLINE REVIEWS, LIVE STREAMING, DAN PROMOTION TERHADAP PURCHASE INTENTION MELALUI CUSTOMER TRUST SEBAGAI VARIABEL INTERVENING (Studi Pada Konsumen Produk Wardah di Kota Semarang) - Clarabelle Putri Rahman, Felicia Cassie; Khasanah, Imroatul (Faculty of Economics and Business Diponegoro University, 2024)
ABSTRACT Currently, Wardah lipstick products are increasingly experiencing challenges due to the large number of competitors. This study discusses the effect of Customer Online Reviews, Live Streaming, and Promotion on Purchase Intention on Wardah lipstick products through mediation of Customer Trust. And so, how the mediating role of Customer Trust on Customer Online Reviews, Live Streaming, and Promotion on Purchase Intention on Wardah lipstick products that have decreased sales. This research uses quantitative methods, with SEM-PLS measuring instruments using the SmartPLS version 4 application with validity and reliability tests and hypothesis testing using bootstrapping. The results of this study indicate that Customer Online Reviews have a positive effect on Customer Trust, Live Streaming has a positive effect on Customer Trust, Promotion has a positive effect on Customer Trust, and Customer Trust has a positive effect on Purchase Intention. Based on the research that has been done, it is known that Customer Online Reviews, Live Streaming, and Promotion affect Customer Trust so that it leads to consumer Purchase Intention which can increase sales of Wardah lipstick products.